The Role of The Young Generation in the Field of Education for Village Development - Wulandari, Icha Septia; Montessori, Maria (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The purpose of this research is to see the role of the younger generation in the field of education for the development of Rejosari Village. This research is qualitative with a Participatory Action Research (PAR) approach. The research data is in the form of educational activities for the younger generation for the development of Rejosari Village. The data sources were obtained from the youth and the people of Rejosari Village. The data collection techniques used were observation, interviews, and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The results of the study found that the educational role of the younger generation in the field of education is as a leader or mobilizer, as well as a tutor or facilitator. Educational activities carried out by the younger generation are managing places to study the Qur’an / TPA, TCI Tutoring, and also Computer Learning. At the stage of implementing the learning program, it is said to be smooth but still not optimal. This teaching and learning activity has not been maximized because there is still a lack of adequate facilities, for example, in the implementation of Tutoring activities, because there is still no special place used as a place for children's learning.